The genomic architecture of resistance to Campylobacter jejuni intestinal colonisation in chickens. (December 2016) - Psifidi, A.; Fife, M.; Howell, J.; Matika, O.; van Diemen, P.; Kuo, R.; Smith, J.; Hocking, P.; Salmon, N.; Jones, M.; Hume, D.; Banos, G.; et al.
Abstract Background Campylobacter is the leading cause of foodborne diarrhoeal illness in humans and is mostly acquired from consumption or handling of contaminated poultry meat. In the absence of effective licensed vaccines and inhibitors, selection for chickens with increased resistance toCampylobacter could potentially reduce its subsequent entry into the food chain.Campylobacter intestinal colonisation levels are influenced by the host genetics of the chicken. In the present study, two chicken populations were used to investigate the genetic architecture of avian resistance to colonisation: (i) a back-cross of two White Leghorn derived inbred lines [(61 x N) x N] known to differ in resistance toCampylobacter colonisation and (ii) a 9th generation advanced intercross (61 x N) line. Results The level of colonisation withCampylobacter jejuni following experimental infection was found to be a quantitative trait. A back-cross experiment using 1, 243 fully informative single nucleotide polymorphism (SNP) markers revealed quantitative trait loci (QTL) on chromosomes 7, 11 and 14. In the advanced intercross line study, the location of the QTL on chromosome 14 was confirmed and refined and two new QTLs were identified located on chromosomes 4 and 16. Pathway and re-sequencing data analysis of the genes located in the QTL candidate regions identified potential pathways, networks and candidate resistance genes. Finally, gene expression analyses were performed for some of the candidate resistance genes to support the results. Conclusion Campylobacter resistance in chickens is a complex trait, possibly involving the Major Histocompatibility Complex, innate and adaptive immune responses, cadherins and other factors. Two of the QTLs forCampylobacter resistance are co-located withSalmonella resistance loci, indicating that it may be possible to breed simultaneously for enhanced resistance to both zoonoses.